Analisis Metode Pembelajaran S3D Terhadap Pengembangan Soft Skill Mahasiswa - wahyudhi sutrisno (Teknoin, 2019)
The university is one of the producers of prospective workers who have an important influence in determining the success of the workforce in pursuing their career path. The university is expected to be able to produce qualified workforce candidates, ready to use, and have hard skills and soft skills. This study aims to analyze the learning methods of the Student Soft Skill Development (S3D) program conducted at Faculty of Industrial Technology, Islamic University of Indonesia. S3D is one of the programs implemented with the aim of developing soft skills possessed by students. This study uses the literature review method where the researcher reads, understands, and compares literature from various sources with the object under study. The conclusion of this research is S3D learning method is in accordance with the theory and the results of other studies regarding soft skills education.